پاکستانی آئین میں غیر مسلم اقلیتوں کے حقوق کا تجزیاتی مطالعہ - Abdullah Ijaz; Prof. Dr. Hammad Lakhvi (الآفاق اسلامی و تحقیقی مجلہ, 2023)
This analytical study delves into the constitutional framework of Pakistan, focusing specifically on the rights and protections afforded to non-Muslim minorities within the country. Pakistan, a nation with a rich tapestry of religious diversity, has grappled with issues related to the safeguarding of the rights of its non-Muslim citizens since its inception. This abstract encapsulates the comprehensive research undertaken to assess the legal and practical dimensions of these rights, highlighting the historical context, constitutional provisions, and their implementation.The study employs a multidisciplinary approach, combining legal analysis, historical context, and sociopolitical considerations to paint a holistic picture of the situation. Key areas of exploration include freedom of religion, cultural preservation, political representation, and access to education and economic opportunities. Through a meticulous review of the relevant articles and amendments in Pakistan's Constitution, as well as an examination of relevant case law and international human rights standards, this research seeks to provide an in-depth understanding of the current status and challenges faced by non-Muslim minorities in Pakistan.Furthermore, the study critically evaluates the extent to which constitutional safeguards are translated into practice and the impact of various sociopolitical factors on the ground. It also sheds light on the evolving discourse surrounding the rights of non-Muslim minorities in Pakistan, especially in the context of changing societal dynamics and global human rights standards.The findings of this research have significant implications for both policymakers and advocates of religious and minority rights. By shedding light on the strengths and weaknesses of the constitutional framework, this study aims to contribute to the ongoing dialogue on religious freedom and minority rights in Pakistan, ultimately promoting a more inclusive and equitable society for all of its citizens.